2016
DOI: 10.1371/journal.pone.0147502
|View full text |Cite
|
Sign up to set email alerts
|

Sustainability in Supply Chain Management: Aggregate Planning from Sustainability Perspective

Abstract: Supply chain management that considers the flow of raw materials, products and information has become a focal issue in modern manufacturing and service systems. Supply chain management requires effective use of assets and information that has far reaching implications beyond satisfaction of customer demand, flow of goods, services or capital. Aggregate planning, a fundamental decision model in supply chain management, refers to the determination of production, inventory, capacity and labor usage levels in the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
28
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(28 citation statements)
references
References 23 publications
0
28
0
Order By: Relevance
“…External stakeholder requirements and pressures were seen as the main driver and motivator for implementation of SSCM and environmental supply chain management (GSCM) practices (Lin, 2013;Luthra et al, 2016;Seuring and Müller, 2008;Somsuk and Laosirihongthong, 2016;Türkay et al, 2016;Yu Xia, 2011;Zhu et al, 2006). Legislative bodies such as the governmental regulators were identified as a highly influential factor for GSCM deployment (Luthra et al, 2016) whereas, Türkay et al (2016) concluded that legislation is imperative for integration of social and environmental considerations into SCM.…”
Section: Sustainable Supply Chain Management -Sscm Research Themesmentioning
confidence: 99%
See 1 more Smart Citation
“…External stakeholder requirements and pressures were seen as the main driver and motivator for implementation of SSCM and environmental supply chain management (GSCM) practices (Lin, 2013;Luthra et al, 2016;Seuring and Müller, 2008;Somsuk and Laosirihongthong, 2016;Türkay et al, 2016;Yu Xia, 2011;Zhu et al, 2006). Legislative bodies such as the governmental regulators were identified as a highly influential factor for GSCM deployment (Luthra et al, 2016) whereas, Türkay et al (2016) concluded that legislation is imperative for integration of social and environmental considerations into SCM.…”
Section: Sustainable Supply Chain Management -Sscm Research Themesmentioning
confidence: 99%
“…The implementation of ISO14001 environmental management system and use of certified suppliers were identified as influential factors for GSCM implementation and effectiveness(Agi and Nishant, 2016;Ansari and Qureshi, 2015) Govindan et al (2014). supported this view, however put forward the argument that ISO14001 implementation, although being an influential factor for environmental sustainability, does not have a significant impact on overall supply chain sustainability performance due to its lack of influence on economic and social dimensions.In general, a consensus has been reached in SSCM literature over a period of time that the incorporation of all three pillars of sustainability (TBL) into SCM is required(Ansari and Qureshi, 2015;Ashby et al, 2012;Awudu and Zhang, 2012;Beske and Seuring, 2014;Gold and Schleper, 2017;Reefke and Sundaram, 2016;Türkay et al, 2016;Winter and Knemeyer, 2013). Considering the traditional focus of organizations on the economic dimension(Gold and Schleper, 2017) and the extant research concentration on the environmental issues (GSCM), the integration of triple bottom line and multi dimensional approaches into the supply chain thinking will provide more balanced, holistic and effective SSCM implementation, mitigating the risk of favouring certain dimensions over the others.Several decision making support models were designed by the literature to facilitate measurement and integration of sustainability into supply chain management activities although only two papers considered all three pillars of sustainability (Chardine-Baumann and Botta-Genoulaz, 2014; Schaltegger and Burritt, 2014).…”
mentioning
confidence: 99%
“…30 One study found cost feedback to physicians, combined with a small departmental financial incentive, was associated with significantly reduced surgical supply costs without negatively affecting patient outcomes. 19 In addition to supporting public health and well-being, adopting best environmental practices also can deliver triple bottom line returns, 62 which reduce costs, 18 optimize operational efficiency, and enhance patient and worker safety. 35 The health care industry, whose mission is to protect and promote health, contributes to the climate crisis-the greatest health threat of the 21st century.…”
Section: Rationalementioning
confidence: 99%
“…al. [33] modified the traditional aggregate production and operations planning approach by considering the environmental and social dimensions, based on the TBL perspective. A closed loop facility location model was proposed by Amin and Zhang [34] in a supply chain network with multiple facilities and multiple products, and was solved by weighted sums and -constraint methods.…”
Section: Multi-objective Modelsmentioning
confidence: 99%